Experimental study on static temperature field effect on standing seam metal roof system. (June 2021) - Wang, Mingming; Ou, Tong; Xin, Zhiyong; Wang, Dayang; Zhang, Yongshan; Cui, Liang
Abstract: Large-span roof structure is widely used in important landmark buildings. This paper presents the experimental investigations of the deformation and stress distribution of standing seam metal roof system (SSMR) under the condition of a uniform temperature field. The experimental results show that with the increase of temperature, the stresses of slab rib, support, bottom and surface of the roof slab increase gradually, in which the maximum stress growth rates are 1.77, 0.87, 0.64, and 1.68, respectively. The minimum stress increase appears at the slab bottom, while the maximum stress increase with a value of 83.7% of yield strength appears at the slab rib. With the enhancement of the constraint boundary, the stress of the two specimens gradually increases. In particular, the stresses increased the most under fixed at both ends constraints. The stresses show significantly different values in different positions of the roof slab. Both the horizontal and vertical displacement of the roof slab increased with the temperature. And the maximum horizontal displacement of the roof slab is respectively 14.85 mm and 20.42 mm (free one end), in which maximum vertical displacement is 2.34 mm and 6.11 mm, respectively (fix two ends).